Promoting knowledge to policy translation for urban health using community-based system dynamics in Brazil - Lidia Maria de Oliveira Morais; Jill Kuhlberg; Ellis Ballard; Katherine Indvik; Solimar Carnavalli Rocha; Denise Marques Sales; Letícia de Oliveira Cardoso; Nelson Gouveia; Amélia Augusta de Lima Friche; Waleska Teixeira Caiaffa (BMC, 2021)
Abstract Background Effectively bridging the knowledge-policy gap to support the development of evidence-based policies that promote health and well-being remains a challenge for both the research and policy communities. Community-based system dynamics (CBSD) is a participatory modelling approach that aims to build stakeholders' capacity to learn and address complex problems collaboratively. However, limited evidence is available about the contributions of CBSD to knowledge-generating and policy processes across sectors and policy spheres. In the context of a multi-country research project focused on creating an evidence base to inform urban health policies across Latin America, a series of CBSD workshops convened stakeholders from research, policy-making, and other backgrounds working in food and transportation systems. Diverse participants were selected aiming to incorporate multiple perspectives relevant to understanding complex urban systems linked to food and transportation. This study focuses on one of these workshops, whose avenue was São Paulo, Brazil, assembling country-based participants representing local, regional, national, and international institutions with multidisciplinary backgrounds linked to food and transportation systems. Objective The aim of this case study is to explore the perceived influence of one of these workshops on attendees' understandings of food and transportation systems and their relationship to healthy urban environments, with attention to the role of the workshop in supporting knowledge to policy translation for urban health. Methods We conducted 18 semi-structured qualitative interviews with attendees one year after their participation in a CBSD workshop held in São Paulo, Brazil. A framework method approach was used to code participants' responses and identify emerging themes. Results Participants reported that the workshop's group model-building activities influenced their understanding of the knowledge-policy process as it relates to food and transport systems. Workshop contributed to participants' (1) abilities to engage with multisectoral stakeholders, (2) construct a shared language and understanding of urban challenges, (3) improve understanding of the interconnectedness across food and transportation systems, (4) facilitate dialogue across sectors, and (5) apply a systems thinking approach within their sector and professional context. Participants continued to draw on the tools developed during the workshop, and to apply systems thinking to their research and policy-making activities. Conclusions CBSD may offer valuable opportunities to connect the research sector to the policy-making process. This possibility may contribute to knowledge to policy translation in the interconnection between the urban context, food and transportation systems, and health.